Pulsed Fluidization of Nanosilica: Rigorous Evaluation of the Efficacy of Pulsation Frequency - Mohammad Asif; Ebrahim H. Al-Ghurabi; Amanullah Fatehmulla (Nanomaterials, 2022)
Assisted fluidization techniques can significantly improve the hydrodynamics of difficult- to-fluidize solids. Among these techniques, the pulsed flow strategy is highly promising owing to its cost-effectiveness and amenability to implementation for largescale processing. Using commercial-grade, highly porous nanosilica that shows strong agglomeration behavior, we implemented the pulsed flow with square-wave pulsation schemes of 0.05, 0.10, and 0.25 Hz frequencies, and compared their effectiveness in each case. Besides the conventional approach of assessing their efficacy using the pressure drop data, we have proposed a new approach in this work that consists of computing the power of the overall pressure drop transient signals. Using the theoretical value, i.e., the effective bed weight per unit area as a reference, the percentage increase in the power was 27 ± 4, 71 ± 5, and 128 ± 4, respectively, for 0.05, 0.10, and 0.25 Hz pulsation frequencies. In fact, the average pressure drop values were substantially higher when the partial bed collapse occurred between successive pulsations when compared with the case of low-frequency pulsations. The pulsation frequency also affected the evolution of local bed dynamics in various bed regions during the expansion and collapse of the bed. Moreover, the local and global pressure transients have shown interesting mutual correlations which were otherwise not evident from their individual transient profiles.